CLINICAL EVALUATION OF RASAYANA EFFECT OF GUDUCHI SVARASA IN APPARENTLY HEALTHY INDIVIDUALS - Singh Mukti Manki Mita; Bhatnagar Shailza (International Journal of Applied Ayurved Research, 2019)
Introduction- The people who appear healthy in fact are accustomed to many health troubles in routine such as digestive problems, low strength, stress and insomnia. In Ayurveda rasayana has been placed under svasthya urjaskara type of class of medicine which are basically intended to promote health of healthy individuals. Guduchi (Tinospora cordifolia) is described as a rasayana which enhances longevity and memory, alleviate diseases resulting in total gain of physical and mental health. Aims and Objectives-To evaluate the effectiveness of Guduchi svarasa in terms of physical and mental health based on different subjective parameters of rasayana in apparently healthy individuals. Materials and Method – Forty apparently healthy individuals were given fresh Guduchi svarasa in the dosage of 40ml/day empty stomach in the morning for 2 months with a follow up period of 4 weeks. Result- The result was found extremely significant in jarana shakti, sharirika bala, mala-pravriti, nidra, dhriti and varna among different subjective parameters. Conclusion-Improvement was seen in overall health in apparently healthy individuals.